Implementation of Mobile Library Services by the West Sulawesi Provincial Library and Archives Service in Motivating Students' Reading Interest in Mamuju Regency - Basri Basri; Yuspiani Yuspiani; Andi Halimah; Muhammad Ramli; Baharuddin Baharuddin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Reading interest is a crucial factor in improving the quality of human resources. However, literacy rates in Indonesia remain low, particularly in remote areas. One innovation to address the access gap is mobile library services. This study evaluated the Sapa Mobile Library in Mamuju Regency, West Sulawesi, focusing on operational conditions, student reading interest developments from 2023 to 2025, and optimization strategies. Using descriptive qualitative methods, the results revealed challenges such as limited fleet, irrelevant collections, inconsistent schedules, and limited outreach to Islamic schools (madrasah). Student reading interest increased at the start of the program but declined due to inconsistent service delivery and a lack of family support. Recommended strategies include fleet rejuvenation, curriculum and culturally-based collection updates, librarian training, expanded outreach, and service digitization. This study proposes a relevant and sustainable inclusive literacy model.